Child sexual abuse: moral panic or state of denial? - Pilgrim, David (Routledge, 2018)
Introduction -- Sleazy politicians -- Conspiracy theories -- Keeping it in the family -- Religious settings -- Trojan horse -- Street life -- Lessons from Down Under -- Is child sexual abuse a moral panic? -- Political defenders -- Protecting children